Solitary Splenic Metastasis of Fallopian Tube Carcinoma: A Case Report and Review of Literature - Cereda, Vittore; Mambella, Giuseppina; Moscato, Michele; Campagna, Domenico; D’Andrea, Mario Rosario (Archives of Clinical and Medical Case Reports, 2022)
Background: Solitary parenchymal splenic metastasis is an unusual event because of its anatomical, histological and physiological features. Breast, ovary, lung, gastric, colorectal cancer and melanoma are the most common tumors from which splenic metastasis may occur and this phenomenon is usually described in disseminated cancers, with a large burden of hematogenous metastases or peritoneal spread. Case Presentation: Here we report a case of a 71-year-old female with an isolated splenic hypodense formation localized in the lower third of the spleen with extracapsular involvement and without any other evidence of secondarisms in other organs. She then performed a splenectomy, followed by histopathological examination which showed a carcinoma with a high-grade papillary growth pattern of likely ovarian origin. Ca125 levels, a pap smear test, a transvaginal ultrasound and a PET/CT scanning were found to be normal. Only a further laparoscopic bilateral adnexectomy revealed an early high-grade serous papillary carcinoma of the left fallopian tube with intratubaric growth, infiltration of the muscle layer and absence of BRCA1/2 mutations at molecular analysis. Thereafter, an adjuvant chemotherapy and radiological controls were performed, without any proof of relapse so far. Conclusion: The reported case is, to the best of our knowledge, the first case of a solitary splenic metastasis arising from an early primary fallopian tube cancer, with no involvement of ovaries, peritoneum and/or other organs. Given the familial history of the patient, in the near future, it would be useful to include the analysis of mutations in ovarian cancer susceptibility genes through multigene panels in order to improve cancer risk management.